Urbanismo de la Hispania “céltica”. Castros y oppida del centro y occidente de la Península Ibérica - Almagro- Gorbea, Martín (Complutum, 1994)
The ‘castros’ or hillforts are esential to understand the social-cultural evolution of the “Celtic” peoples of the iberian Peninsula wich occuped their central and western parts. They begun in a ancient polimorfous Late Bronze Age “proto celtic” substratum which during the I millennium B.C. evolued towards proto-urban cultures with indirect mediterranean influences arrived through Tundetanians and Iberians. These evolution give rise to oppida and civitates which emerged during the V to II century B.C. to control broader territories and more complex societies characteristic of the “Celtic” and related peoples which confronted and were absorbed by Rome. But this preroman urbanism explain the lanscape, habitat and communal traditions subsisted until today, specialy in mountain and marginal areas of the Meseta.